Strategies For Developing The Competence Of Tutors In Music Course Institutions - Jean Jessica; Dety Mulyo Harsono (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
Developing tutor competence in music course institutions is essential in improving the quality of non-formal music learning. This study aimed to formulate effective strategies to improve teachers' pedagogical, technical, and professional skills. The method used is a descriptive qualitative study with a literature review approach and policy analysis of music education institutions. Data were obtained from various sources of documentation, interviews with course managers, and a review of teacher development practices in relevant institutions. The analysis results show that effective development strategies include preparing career maps, continuous training, utilizing learning technology, and empowering professional communities. Rotation programs, external partnerships, and support for teaching innovation through classroom action research have also strengthened teacher capacity. Discussions emphasized the importance of collaboration, access to digital resources, and recognition of achievement as key motivators.  In conclusion, integrated and adaptive strategies can create a sustainable competency development ecosystem. Recommendations include institutional policy support, investment in training, and establishing innovation forums as part of a more dynamic and impactful teacher development system.